Decision Support System For New Employee Acceptance Using AHP and SAW Method - Rahadian Fatta Batubara; Abdul Halim Hasugian (INTECOMS: Journal of Information Technology and Computer Science, 2023)
The acceptance of employees in every company is an activity that always takes place in a certain period or incidentally. This recruitment process requires decision-making as well as other decision-making processes in different contexts. The selection of these future collaborators sometimes becomes difficult when there are many candidates from diverse backgrounds and when the acceptance criteria set are sometimes complex and sometimes contradictory. By solving these problems, this research provides a solution by developing a system using the application of AHP and SAW methods. The system development method is the waterfall model. Research results show that The decision support system for hiring employees at PT Naufal Indo Raya using Analytic Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods was developed using the web. And the results of applying Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) methods as employee hiring methods in the developed system have the same results in the evaluation process or of classification. Based on this system, Wahyu is known to have received the top rank with an overall score (AHP) of 917.1373 and a Vi(%) (SAW) value of 96.39%. In second place was obtained by Budi with an aggregate value (AHP) of 874.7115 and a Vi(%) value (SAW) of 93.29%. And in third place was obtained by Rudi with an aggregate value (AHP) of 870.6369 and a Vi(%) (SAW) value of 92.65%